A supremum-type RESET test for binary choice models - Ramalho, E. A.; Ramalho, J. J. S.; Murteira, J. M. R. (Economics Bulletin, 2012)
This note introduces a supremum -type RESET statistic for testing the specification of binary choice regression models.A Monte carlo simulation study reveals very promising results for the proposed statistic.